Kesulitan Siswa Dalam Menyelesaikan Soal Aljabar - Lana Sugiarti - (UNIKA SANTU PAULUS RUTENG, 2020)
This study aims to determine the difficulties experienced by students in solving the problem of algebraic form concepts. This type of research is a qualitative research with a case study approach. Data collection methods used include algebraic and open questionnaire operation tests. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results of the study stated that there were difficulties students in working on algebra questions related to the concept. Difficulties experienced by students related to the concept of (1) determining variables and constants; and (2) do not yet understand the concept of division in algebraic material.